A resilient health system? Well-child visits before and after COVID-19 in Chile - Carolina Acevedo (Frontiers in Pediatrics)
IntroductionChildhood is a critical period where access to medical controls and health policies can severely affect health equity.ObjectivesAnalyzed to subnational Chile health system's resilience in the face of the COVID-19 pandemic regarding child health. The focus of the research was to assess the performance of Chile Crece Contigo's social policy, specifically the Well-Child Visit Program, which provides health checks to one million children annually through the primary health network.MethodsUsing a subnational post-pandemic recovery rate, a regression analysis with municipal controls was performed to observe recovery facilitators. A percentage based on the total child population was obtained for the commune of each country and year of study (2015–2022). Data was collected from the Monthly Statistical Reports (REM) of the Ministry of Health, the Socioeconomic Characterization Survey (CASEN), and the National Institute of Statistics of Chile (INE).ResultsRecovery rate at the national level was −3.2%. However, when examining the subnational reality, it was found that 66% of Chilean municipalities are unable to reach pre-pandemic figures and are also territorially concentrated in certain regions of the country. The analysis revealed that municipalities with the worst recovery rate results had negative health expenditure per population.ConclusionsExamining this phenomenon through a subnational lens invites contemplation on the importance of contextualizing it within the theoretical framework of health system resilience. The child health system's capacity must build knowledge based on developing public policies, governance, financing, and coordination in the territories to overcome the crisis.